Transdermal Buprenorphine: utilization trends in United Kingdom primary care practices - Zin, Che Suraya (2012)
Background information: The utilization of transdermal buprenorphine rapidly increased in the past 10 years, since the first item launched in 2002. The increase utilization was suggested mainly causing by expending use for chronic pain control.